2017
DOI: 10.3390/atmos8110230
|View full text |Cite
|
Sign up to set email alerts
|

A High Resolution Spatiotemporal Model for In-Vehicle Black Carbon Exposure: Quantifying the In-Vehicle Exposure Reduction Due to the Euro 5 Particulate Matter Standard Legislation

Abstract: Abstract:Several studies have shown that a significant amount of daily air pollution exposure is inhaled during trips. In this study, car drivers assessed their own black carbon exposure under real-life conditions (223 h of data from 2013). The spatiotemporal exposure of the car drivers is modeled using a data science approach, referred to as "microscopic land-use regression" (µLUR). In-vehicle exposure is highly dynamical and is strongly related to the local traffic dynamics. An extensive set of potential cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…For instance, Ref. [69] found that in-vehicle exposure is highly dynamic and related to local traffic dynamics. A fitted diurnal pattern indirectly explains the complex diurnal variability of the exposure due to the non-linear interaction between traffic density and distance to the preceding vehicles.…”
Section: Transport Microenvironmentsmentioning
confidence: 99%
“…For instance, Ref. [69] found that in-vehicle exposure is highly dynamic and related to local traffic dynamics. A fitted diurnal pattern indirectly explains the complex diurnal variability of the exposure due to the non-linear interaction between traffic density and distance to the preceding vehicles.…”
Section: Transport Microenvironmentsmentioning
confidence: 99%
“…This issue is analysed by Jereb et al [34], who quantify BC concentrations at chosen sites and cycling routes in Slovenia and conclude that exposure can indeed be reduced through adequate urban and traffic planning and management. Dekoninck & Int Panis [35], on the other hand, focus on the influence of transportation modes and assess the exposure of car drivers to BC with a microscopic land-use regression approach, taking into account regulatory interventions (e.g., the Euro 5 Particulate Matter Standard). This kind of exposure estimate is especially relevant for epidemiologists and policy makers.…”
Section: Exposure and Toxicitymentioning
confidence: 99%